Reputation: 13814
Perl allows ...
$a = "fee";
$result = 1 + f($a) ; # invokes f with the argument $a
but disallows, or rather doesn't do what I want ...
s/((fee)|(fie)|(foe)|(foo))/f($1)/ ; # does not invoke f with the argument $1
The desired-end-result is a way to effect a substitution geared off what the regex matched.
Do I have to write
sub lala {
my $haha = shift;
return $haha . $haha;
}
my $a = "the giant says foe" ;
$a =~ m/((fee)|(fie)|(foe)|(foo))/;
my $result = lala($1);
$a =~ s/$1/$result/;
print "$a\n";
Upvotes: 1
Views: 153
Reputation: 118138
See perldoc perlop. You need to specify the e
modifier so that the replacement part is evaluated.
#!/usr/bin/perl
use strict; use warnings;
my $x = "the giant says foe" ;
$x =~ s/(f(?:ee|ie|o[eo]))/lala($1)/e;
print "$x\n";
sub lala {
my ($haha) = @_;
return "$haha$haha";
}
Output:
C:\Temp> r the giant says foefoe
Incidentally, avoid using $a
and $b
outside of sort
blocks as they are special package scoped variables special-cased for strict.
Upvotes: 12